 Let the two numbers be a and b.
a + b = 2 (a  b)
a + b = 2a  2b
3b = a
but b= 10
a = 30
Ans : E
 The given expression is
Ans : C
 n (A È B) = n(A) + n(B)  n(A Ç B)
But u = n (A È B) + n (A È B)’
n ( A È B) = 42 + 45  22
n (A È B) = 65
85 = 65 + n (A È B)’
n (A È B)’ = 20
Ans : B

Since the letters represent consecutive integers, moving backwards from f to b
one gets 4 units.
\ f  b = 6  2 = 4
Ans : B

Since the letters represent consecutive integers, the sum c + d + g = 3c + 5
\ c + d + g = c + c + 1 + c + 4
= 3c + 5
Ans : A

Since the letters represent consecutive integers, consider
b = a + 1, c = a + 2, and d = c + 1
To find d^{2}  b^{2}
Substituting the values of d as (c + 1) and b as (a + 1)
(c + 1)^{2}  (a + 1)^{2} = c^{2} + 2c + 1  a^{2}  2a  1
= c^{2}  a^{2} + 2 ( c  a)
= 24 + 2 ( c  a) [Since c^{2}  a^{2} = 24]
But c = a + 2
\ d^{2}  b^{2}^{ } = 28
Ans : E

Ans : C
[next page]

Index
Test 3
Section 1: Verbal Reasoning
Section 2: Mathematical Reasoning
Section 3: Verbal Reasoning
Section 4: Mathematical Reasoning
Section 5: Reading Comprehension
Section 6: Mathematical Reasoning
Section 7: Mathematical Reasoning
Answer Key To Test 3
Answer Explanation To Test 3
Section 1: Verbal Reasoning
Section 2: Mathematical Reasoning
Section 3: Verbal Reasoning
Section 4: Mathematical Reasoning
Section 5: Reading Comprehension
Section 6: Mathematical Reasoning
Section 7: Mathematical Reasoning
Test 4 